2009
DOI: 10.1586/erv.09.5
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion-based adjuvants for influenza vaccines

Abstract: The ongoing epizootic of highly pathogenic avian H5N1 influenza and its direct transmissibility and high pathogenicity in humans has led to renewed interest in the development of influenza vaccines with enhanced immunogenicity. Influenza vaccines are currently under development against influenza strains that are potentially pandemic threats, such as H5N1, as well as against the current seasonal influenza strains for use in populations susceptible to severe influenza disease. Influenza vaccines may be generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 46 publications
0
74
0
Order By: Relevance
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. (Vahlenkamp et al, 2008) (Vasileiou et al, 2008) Study population (Veits et al, 2006) Not relevant outcomes (Vela et al, 2012) Not relevant outcomes (Velumani et al, 2008) Not relevant outcomes (Vergara-Alert et al, 2011) Not relevant outcomes (Vesikari et al, 2012) Study population (Vieira et al, 2009) Territory (Vivancos et al, 2011a) Study population (Vivancos et al, 2011b) Study population (Voeten et al, 2009) Not relevant outcomes (Vogel et al, 2009) Study population (Walker et al, 2010) Territory (Walker et al, 2012) Territory (H. Study population (Wan, 2012) Territory (X.-F. ) Territory Study population Territory ) Territory Not relevant outcomes Not relevant outcomes (Werner and Harder, 2006) Language (Whiteley et al, 2007) Study population (Wilson et al, 2013) Territory (Wu et al, 2006) Study population (Wu et al, 2015) Territory Not relevant outcomes (Xing et al, 2008) Not relevant outcomes (Yalcin et al, 2010) Not relevant outcomes (Yamaguchi et al, 2010) Territory Territory (Yang et al, 2012) Study population (Yang et al, 2007) Study population (Yassine et al, 2013) Study population The present document has been produced and adopted by the bodies identified above as authors. This task has been carried out exclusively by the authors in the context of a contract between the European Food Safety Authority and the authors, awarded following a tender procedure.…”
Section: Citation Reason Of Exclusionmentioning
confidence: 99%
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. (Vahlenkamp et al, 2008) (Vasileiou et al, 2008) Study population (Veits et al, 2006) Not relevant outcomes (Vela et al, 2012) Not relevant outcomes (Velumani et al, 2008) Not relevant outcomes (Vergara-Alert et al, 2011) Not relevant outcomes (Vesikari et al, 2012) Study population (Vieira et al, 2009) Territory (Vivancos et al, 2011a) Study population (Vivancos et al, 2011b) Study population (Voeten et al, 2009) Not relevant outcomes (Vogel et al, 2009) Study population (Walker et al, 2010) Territory (Walker et al, 2012) Territory (H. Study population (Wan, 2012) Territory (X.-F. ) Territory Study population Territory ) Territory Not relevant outcomes Not relevant outcomes (Werner and Harder, 2006) Language (Whiteley et al, 2007) Study population (Wilson et al, 2013) Territory (Wu et al, 2006) Study population (Wu et al, 2015) Territory Not relevant outcomes (Xing et al, 2008) Not relevant outcomes (Yalcin et al, 2010) Not relevant outcomes (Yamaguchi et al, 2010) Territory Territory (Yang et al, 2012) Study population (Yang et al, 2007) Study population (Yassine et al, 2013) Study population The present document has been produced and adopted by the bodies identified above as authors. This task has been carried out exclusively by the authors in the context of a contract between the European Food Safety Authority and the authors, awarded following a tender procedure.…”
Section: Citation Reason Of Exclusionmentioning
confidence: 99%
“…12,13,21,22,[44][45][46]50,51 Their nanoscale size, with all three dimensions ranging from 0.1 to 100 nm, happens to be the size range of the fundamental building blocks of biology (including DNA, proteins, viruses, ultrastructures and organelles). Thus, the ways in which engineered nanomaterials may interfere with the function of the host immune system and how these immunomodulatory activities may affect vaccines are increasingly important questions.…”
Section: Immunomodulatory Effects Of Nanomaterialsmentioning
confidence: 99%
“…In particular, MF59 has shown more potent adjuvant activity than alum in inducing humoral and T helper type 1 (Th1) immune responses. 21,22 Other nano-adjuvants, including virus-like nanoparticles (VLNs) (15-30 nm), poly(lactide-co-glycolide) (PLGA) nanoparticles (100-200 nm), cationic liposomes, nanoemulsion W 805 EC (400 nm), and cholesterol-bearing nanogel (30-40 nm), are under investigation in clinical trials nearing completion. 11 Emerging evidence shows that the ability to engineer and integrate desired properties and functions into nanomaterials will significantly contribute to generating novel adjuvants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many studies have focused on increasing the immunogenicity of M2-and HA2-based vaccines with various vaccine adjuvants (10). Although several hundred different adjuvants have been tested for use in novel vaccine design during the last few decades, the vast majority have not been successfully approved for human use, with limitations including lack of efficacy, unacceptable local or systemic toxicity, difficulty of manufacturing, poor stability, and prohibitive cost (10)(11)(12)(13). For this reason, until recently, aluminum-based mineral salts have been the most widely used adjuvant in human vaccines.…”
mentioning
confidence: 99%